1979
DOI: 10.1207/s15327752jpa4303_4
|View full text |Cite
|
Sign up to set email alerts
|

Conception and Representation of Space in Human Figure Drawings by Schizophrenic and Normal Subjects

Abstract: Seventy hospitalized schizophrenic adults, and 71 normal subjects were given a test consisting of six human figure drawings, arranged in a thematic sequence from a self-portrait to a drawing of a person. The structural components of each human figure were scored and analyzed in an attempt to validate their projective character and to examine influence of psychopathology on cognition. Findings indicated similar constructional trends for both groups, with differences particular to sex, rather than a diagnostic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

1982
1982
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
6
2
Order By: Relevance
“…John (1974) found that recently hospitalized schizophrenics had much less symmetrical drawings than normal controls on four measures of symmetry. By contrast, schizophrenics and normals did not vary in Cvetkovic's (1979) study.…”
Section: Symmetrycontrasting
confidence: 58%
See 2 more Smart Citations
“…John (1974) found that recently hospitalized schizophrenics had much less symmetrical drawings than normal controls on four measures of symmetry. By contrast, schizophrenics and normals did not vary in Cvetkovic's (1979) study.…”
Section: Symmetrycontrasting
confidence: 58%
“…Kokonis (1972a) reported that male schizophrenics omitted limbs more than normal controls. By contrast, Cvetkovic (1979) found no differences in omissions between schizophrenics and normals. Dudley et al (1973; reported no differences between schizophrenics and other diagnostic groups, nor between subjects high on Sc on the MMPI and those scoring low.…”
Section: Omissioncontrasting
confidence: 57%
See 1 more Smart Citation
“…For example, Dudley, Craig, Mason, and Hirsch (1976) found that depressed individuals were less likely than nondepressed individuals to draw faces in profile, directly contradicting one of Machover's hypotheses. Again contra Machover, Cvetkovic (1979) reported that schizophrenics were less likely than normals to draw disembodied heads. Moreover, in a review of research on human figure drawing signs and anxiety, Handler and Reyher (1965) found that 30 of 255 findings were statistically significant in the direction opposite from those predicted (see Riethmiller & Handler, 1997a, for discussions of these negative findings).…”
Section: Human Figure Drawing Methodsmentioning
confidence: 99%
“…With time, more empirical studies appeared that tentatively pointed to possible correlations of spatial attributes of drawings with measures of personality and psychopathology (e.g., Buck, 1966;Jolles & Beck, 1953;Koppitz, 1968;Marzolf & Kirchner, 1972). However, early overviews of the validity of such findings were really not very reassuring (e.g., Cvetkovic, 1979;Ogdon, 1967;Roback, 1968). Little consistent data could be mustered to support clear-cut statements about the meanings of various spatial asymmetries in drawings.…”
Section: Motoric Variablesmentioning
confidence: 99%